Identifying gaps in maternal knowledge and care-seeking for neonatal health: A mixed methods study in rural pregnant women - M Yogesh; B M Bhavana; Nanveet Padhiyar; Rohankumar Gandhi; Swati Misra (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Knowledge of neonatal danger signs is crucial for timely care-seeking and improved newborn survival. This study assessed this knowledge among pregnant women in rural western Gujarat. MATERIALS AND METHODS: A mixed methods study was conducted among 390 pregnant women selected through a two-stage sampling procedure. Quantitative data were collected using a structured questionnaire. Qualitative data were gathered via in-depth interviews with 20 purposively sampled women. Logistic regression identified determinants of knowledge. Thematic analysis was done for qualitative data. RESULTS: The majority of women were young (220, 56.5% ≤25 years), literate (333, 85%), and from rural backgrounds (320, 82%). Overall, 232 (59.5%) knew about cord care, and 301 (77.2%) correctly identified breastfeeding initiation time. Recognition of key danger signs such as fever (311, 79.7%), vomiting (292, 74.8%), and jaundice (275, 70.5%) was high, but only 70 (18%) identified chest in-drawing. Multiparity (adjusted odds ratio (AOR): 1.4, 95% confidence interval (95% CI): 1.2-3.9), lower age (AOR: 3.8, 95% CI: 2.4-5.8), education (AOR: 3.1, 95% CI: 1.5-6.4), inadequate counseling (AOR: 2.2, 95% CI: 1.82-5.190), and normative delivery (AOR: 2.4, 95% CI: 1.16-5.006) were associated with poor knowledge. Qualitative findings revealed reliance on informal sources, family elders, and financial constraints as key barriers along with limited comprehension of some danger signs. CONCLUSION: Focused interventions via health workers, family members, and community platforms are needed to increase neonatal danger signs awareness among vulnerable women in the region to enable timely care-seeking.